2012
DOI: 10.1002/cncr.27543
|View full text |Cite
|
Sign up to set email alerts
|

The use of single‐agent sorafenib in the treatment of advanced hepatocellular carcinoma patients with underlying Child‐Pugh B liver cirrhosis

Abstract: BACKGROUND: This study explored the efficacy, tolerability, and survival benefits of using sorafenib in patients with Child‐Pugh class B (CPB) cirrhosis. METHODS: Patients with advanced hepatocellular carcinoma who were treated with sorafenib at Queen Mary Hospital, Hong Kong, China, were analyzed retrospectively. Treatment outcomes were analyzed according to their respective Child‐Pugh status. Patients with CPB disease were further divided into CPB7 (those with a score of 7) and CPB8‐9 (a score of 8 or 9) sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 18 publications
3
53
3
Order By: Relevance
“…The most likely interpretation was the small sample size in the subgroups CP-6 and CP-7 (CP-6: n 5 12 vs. n 5 11; CP-7: n 5 10 vs. n 5 10). Those results demonstrated a trend indicating that sorafenib monotherapy might be more suitable for HCC patients with MPVTT and in the CP-6 or CP-7 subgroups than combination therapy of sorafenib and TACE, for the following reasons: (a) The combination therapy may exacerbate liver ischemic damage in patients with MPVTT; (b) a poor hepatic reserve increases the risk for irreversible hepatotoxicity after TACE caused by chemotherapy drugs and lipiodol or embolization agents, especially in the patients with MPVobstruction [9,25,26]; (c) patients with a CP score of 6 or 7 tolerated sorafenib well and benefited from it [27]. This finding is important and a large prospective trial should be explored to confirm it.…”
Section: ©Alphamed Press 2015mentioning
confidence: 99%
“…The most likely interpretation was the small sample size in the subgroups CP-6 and CP-7 (CP-6: n 5 12 vs. n 5 11; CP-7: n 5 10 vs. n 5 10). Those results demonstrated a trend indicating that sorafenib monotherapy might be more suitable for HCC patients with MPVTT and in the CP-6 or CP-7 subgroups than combination therapy of sorafenib and TACE, for the following reasons: (a) The combination therapy may exacerbate liver ischemic damage in patients with MPVTT; (b) a poor hepatic reserve increases the risk for irreversible hepatotoxicity after TACE caused by chemotherapy drugs and lipiodol or embolization agents, especially in the patients with MPVobstruction [9,25,26]; (c) patients with a CP score of 6 or 7 tolerated sorafenib well and benefited from it [27]. This finding is important and a large prospective trial should be explored to confirm it.…”
Section: ©Alphamed Press 2015mentioning
confidence: 99%
“…TTP was 4 and 2 months (p = 0.0045), while OS was 8.4 and 3.2 months (p = 0.0007) in patients with CPA and CPB, respectively. Another retrospective study by Chiu et al explored the efficacy, tolerability, and survival benefits of sorafenib in 64 patients with CPB liver function (15). The patients with CPB were divided into CPB7 (with a CPB score of 7) and CPB8-9 (with a CPB score of 8 and 9) subgroups and compared with those with CPA.…”
Section: Other Questions About Sorafenib Usagementioning
confidence: 99%
“…While the incidence of HCC continues to rise, the overall 5-year survival rate remains extremely low at <12% [2]. Though diagnosis with early-stage HCC provides opportunities for several potentially curative treatment options [4], presentation with advanced HCC (Barcelona Clinic Liver Cancer [BCLC] Stage C) was historically met with limited treatment options and poor prognosis [5]. Until recently, there was no systemic therapy demonstrated to effectively treat individuals with advanced HCC [6].…”
Section: Introductionmentioning
confidence: 99%
“…Since the approval of sorafenib, studies have focused primarily on the safety and efficacy of this new molecular-targeted therapy in single-institution, clinical settings [5,13,14]. While these studies have each demonstrated clinical benefit in treating advanced HCC [5,13,14], others note the need to balance this opportunity with the potential for side effects and high treatment costs in the community setting [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation